Preparing design students for strategic design - Rasmussen, Jørgen; Mortensen, Bo Schiønning; Jensen, Birgitte Geert (FormAkademisk, 2012)
This paper deals with how the visual approach from a design process can help inform companies about future opportunities at a strategic level. The paper follows an innovation project where design students worked with five companies at a 1-day workshop and with one company through a 2-week project. In both processes the students worked visually with mapping and making sense of large amounts of data that may influence the company’s strategy. They also synthesized these finding by creating conceptual suggestions for the company’s future products. This paper discusses the lessons learned from the innovation project and reflects on which new knowledge, methods and techniques designers should be aware of when participating in multidisciplinary strategic processes and new educational initiatives. This paper shows how the design profession’s traditional visual tools and methods for concept development can be used to facilitate discussions for companies facing strategic challenges. It also underlines the importance of rethinking design skills and communication when moving into strategic processes.